Novel 1d Cui Coordination Polymer Using Phosphorus-Nitrogen Ligands, Active in Aerobic Oxidation of Cyclohexene - Moya-Duran, S; Moya-Duran, S (Elsevier B.V., 2023)
This work reports the synthesis and characterization of a novel copper(I) coordination polymer, the first one containing a phosphorus-nitrogen ligand, [Cu(κ2-P,N-(diphenylphospino)pyrimidine-2-amine)2Cl]n. This coordination polymer acts as catalyst under homogeneous conditions using molecular oxygen as oxidant. (5 bar and 40 to 120 °C). The catalyst shows high conversion for several substrate/catalyst ratio values (400/1 to 12800/1), and the reaction takes place in the absence of additional solvent with the advantages that this entails. The reported system shows 80% conversion for the cyclohexene oxidation in only 15 min of reaction, using a high substrate/catalyst ratio of 3200/1 with turnover number of 10240 h−1. The catalyst only looses 13% of conversion after 4 cycles. The study suggests a radical mechanism assisted by the catalyst that favors the formation of two major products, 2-cyclohexen-1-one and 2-cyclohexen-1-ol. © 2023